Kendala dan Strategi Pengembangan Kelapa di Distrik Taroi Kabupaten Teluk Bintuni - Rumainum, Inna Martha; Musaad, Ishak; Ningsih, Ratna L.; Makai, Yonatan (Jurnal Pertanian Khairun, 2024)
Taroi District is one of the districts in Teluk Bintuni Regency which is also known as a shrimp producer. Therefore, almost all the people of Taroi District work as fishermen. Shrimp production is greatly influenced by climatic factors so that there is a shrimp fishing season. In the non-shrimp fishing period, the community experienced difficulties in maintaining stable economic conditions. Coconut trees grow abundantly in the Taroi District area, from the coast to the mainland. However, the utilization of coconut commodities can be said to be very low. The main obstacle in developing coconut commodities is limited market access. The geographical location of Taroi District which is far from the district capital causes high transportation prices so that people are unable to market coconuts. Several strategies that can be used to overcome these obstacles are by 1) improving the quality of fruit through the creation of coconut plantations in dry areas, 2) variations in processed coconut products (virgin coconut oil, coconut oil, nata de coco, coconut honey, charcoal briquettes and cocopeat) and 3) availability of transportation and market access.Keywords: Coconut, Taroi District, Teluk Bintuni Regency